2011
DOI: 10.1016/j.jtcvs.2011.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Eight hours of cold static storage with adenosine and lidocaine (Adenocaine) heart preservation solutions: Toward therapeutic suspended animation

Abstract: We report a 78% return of cardiac output, 90% to 100% return of developed pressures, and 101% to 104% return of heart rate after 8 hours of cold static storage using normokalemic, adenosine, lidocaine, melatonin, and insulin preservation solution in the isolated rat heart compared with 55% cardiac output with polarizing adenosine-lidocaine cardioplegia alone, 4% cardiac output with Custodiol-HTK, and 25% cardiac output in Celsior preservation solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 40 publications
1
18
1
Order By: Relevance
“…Many of us still hope for a magic adenosine bullet. These present data from Granfeldt et al (3) add to other promising myocardial protective effects for adenosine-related compounds both in animal models (12) and in patients (13) and should stimulate a new generation of investigators. We can be cautiously optimistic, but it is appropriate to point out that in the past 40 yrs, there have been numerous studies showing benefit with several other adenosine regulating agents (alone or in combination with hypertonic resuscitation) in various hemorrhagic shock models, but none have translated into clinical success.…”
Section: Referencesmentioning
confidence: 57%
“…Many of us still hope for a magic adenosine bullet. These present data from Granfeldt et al (3) add to other promising myocardial protective effects for adenosine-related compounds both in animal models (12) and in patients (13) and should stimulate a new generation of investigators. We can be cautiously optimistic, but it is appropriate to point out that in the past 40 yrs, there have been numerous studies showing benefit with several other adenosine regulating agents (alone or in combination with hypertonic resuscitation) in various hemorrhagic shock models, but none have translated into clinical success.…”
Section: Referencesmentioning
confidence: 57%
“…Its role in heart preservation is currently being investigated. Results from Dobson et al showed favourable recovery of cardiac parameters after six hours of cold storage in AL solution [67,68].…”
Section: Organ Preservationmentioning
confidence: 99%
“…Attending to cardiac transplantation, preservation fluids also play a pivotal role in graft survival. A solution consisting of melatonin (100 mmol/L), adenosine (400 μmol/L), lidocaine (1000 μmol/L), and insulin (0.01 IU/mL) was compared with adenosine-lidocaine cardioplegia with low Ca 2+ /high Mg 2+ concentration levels, HTK solution, and Celsior solution (Rudd & Dobson 2011). The authors observed a higher recovery of aortic flow and coronary flow by using the melatonin preservation solution compared with other treatments.…”
Section: Preservation Solutionsmentioning
confidence: 99%